Analisis Kinerja Aparatur Sipil Negara Di Dinas Perumahan dan Kawasan Permukiman Kabupaten Minahasa Tenggara - Rumambi, Githa; Wuisan , Yesita (GEMA EKONOMI, 2023)
The State Civil Apparatus plays an important role in achieving the success of organizational goals. Performance appraisal is a very important activity because it can be used as a measure of the success of an organization in achieving its mission. With the employee performance appraisal, performance improvement will be achieved in a better direction. State civil servants who do their jobs on time and quickly definitely have high performance. Employee performance is also a determining factor in efforts to improve service to the community. The purpose of this study is to analyze the performance of employees in the Housing and Settlement Area Office of Southeast Minahasa Regency. By using descriptive qualitative methods and data collection using observation and interviews. The results of the study show that the performance of employees at the Housing and Settlement Area Office of Southeast Minahasa Regency is already in the good category. Performance indicators are tools or media used to measure the level of success of an agency in achieving its goals and objectives. Employee performance is influenced by indicators based on quantity, working time, quality and work assessment. It can be concluded that employee performance has an important role in increasing the work results of employees at the Housing and Settlement Area Office of Southeast Minahasa Regency.